Alterations of the spindle checkpoint pathway in clinicopathologically aggressive CpG island methylator phenotype clear cell renal cell carcinomas. Issue 11 (30th June 2015) - Arai, Eri; Gotoh, Masahiro; Tian, Ying; Sakamoto, Hiromi; Ono, Masaya; Matsuda, Akio; Takahashi, Yoriko; Miyata, Sayaka; Totsuka, Hirohiko; Chiku, Suenori; Komiyama, Motokiyo; Fujimoto, Hiroyuki; et al.
Abstract : CpG‐island methylator phenotype (CIMP)‐positive clear cell renal cell carcinomas (RCCs) are characterized by accumulation of DNA hypermethylation of CpG islands, clinicopathological aggressiveness and poor patient outcome. The aim of this study was to clarify the molecular pathways participating in CIMP‐positive renal carcinogenesis. Genome (whole‐exome and copy number), transcriptome and proteome (two‐dimensional image converted analysis of liquid chromatography‐mass spectrometry) analyses were performed using tissue specimens of 87 CIMP‐negative and 14 CIMP‐positive clear cell RCCs and corresponding specimens of non‐cancerous renal cortex. Genes encoding microtubule‐associated proteins, such as DNAH2, DNAH5, DNAH10, RP1 and HAUS8, showed a 10% or higher incidence of genetic aberrations (non‐synonymous single‐nucleotide mutations and insertions/deletions) in CIMP‐positive RCCs, whereas CIMP‐negative RCCs lacked distinct genetic characteristics. MetaCore pathway analysis of CIMP‐positive RCCs revealed that alterations of mRNA or protein expression were significantly accumulated in six pathways, all participating in the spindle checkpoint, including the "The metaphase checkpoint ( p  = 1.427 × 10 −6 ), " "Role of Anaphase Promoting Complex in cell cycle regulation ( p  = 7.444 × 10 −6 )" and "Spindle assembly and chromosome separation ( p  = 9.260 × 10 −6 )" pathways. Quantitative RT‐PCR analysis revealed that mRNA expression levels for genes included in such pathways, i.e ., AURKA, AURKB, BIRC5, BUB1, CDC20, NEK2 and SPC25, were significantly higher in CIMP‐positive than in CIMP‐negative RCCs. All CIMP‐positive RCCs showed overexpression of Aurora kinases, AURKA and AURKB, and this overexpression was mainly attributable to increased copy number. These data suggest that abnormalities of the spindle checkpoint pathway participate in CIMP‐positive renal carcinogenesis, and that AURKA and AURKB may be potential therapeutic targets in more aggressive CIMP‐positive RCCs. Abstract : What's new? CpG‐island methylator phenotype (CIMP)‐positive clear cell renal cell carcinomas (RCCs) are characterized by an accumulation of DNA hypermethylation of CpG islands, clinicopathological aggressiveness, and poor patient outcome. The molecular pathways responsible for generating CIMP‐positive clear cell RCCs, however, remain unclear. Based on an integrated multilayer omics approach including genome, transcriptome, and proteome analyses, here the authors show that abnormalities in the spindle checkpoint pathway participate in CIMP‐positive renal carcinogenesis. The results also suggest the aurora kinases AURKA and AURKB as potential therapeutic targets in more aggressive CIMP‐positive RCCs.